A Rapid Method for the Detection of Diarrhetic Shellfish Toxins and Azaspiracid Shellfish Toxins in Washington State Shellfish by Liquid Chromatography Tandem Mass Spectrometry. (19th April 2020) - Yang, Li; Singh, Avi; Lankford, Shelley K; Stuart, James; Rice, Daniel; Wu, Wen-Hsin; Hungerford, James M
Abstract: Background: Diarrhetic shellfish toxins (DSTs) in domestic shellfish and azaspiracids (AZAs) in imported products are emerging seafood safety issues in the United States. In addition to causing gastrointestinal illnesses, some of these toxins are also carcinogenic and genotoxic. Efficient analytical strategies are needed for their monitoring in U.S. domestic and imported shellfish. Objective: In the US, DSTs and AZAs are the only lipophilic shellfish toxins addressed in regulations. Streamlining of existing methods for several classes of lipophilic toxins, based on liquid chromatography coupled with triple quadrupole mass spectrometry, was pursued. Method: The resulting simplified LC-MS/MS method is focused on the separation and detection of just the AZAs and total DSTs using a C18 Hypersil gold column. Filter vials are used to expedite and simplify sample handling. Results: The method has a run time of 7.25 min. LOQs for the AZAs and DSTs in shellfish were 0.3–0.4 µg/kg. Recoveries (AZAs and total DSTs) for three spiking levels in three matrixes ranged from 68 to 129%. Trueness was established using certified reference materials. Method equivalence was established using shellfish provided blind by the Washington State Department of Health Public Health Laboratory (WA DOH PHL). Data obtained from these samples agreed well with data from another LC-MS/MS method used in harvest control by WA DOH PHL (R = 0.999; P  < 0.0001). Conclusions: The LC-MS/MS method described offers more rapid sample handling and has excellent sensitivity, linearity, and repeatability.